2009
DOI: 10.1186/1746-1448-5-1
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of seasonal phytoplankton distribution in prairie saline lakes of the northern Great Plains (U.S.A.)

Abstract: Seasonal changes in freshwater phytoplankton communities have been extensively studied, but key drivers of phytoplankton in saline lakes are currently not well understood. Comparative lake studies of 19 prairie saline lakes in the northern Great Plains (USA) were conducted in spring and summer of 2004, with data gathered for a suite of limnological parameters. Nutrient enrichment assays for natural phytoplankton assemblages were also performed in spring and summer of 2006. Canonical correspondence analysis of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
8
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 23 publications
(24 reference statements)
2
8
0
1
Order By: Relevance
“…The absence of Top-Down effects and predominance of Bottom-Up forces in saline water systems, have been experimentally proved by Salms et al (2009) in the US saline lakes and Rejas et al (2012) in Bolivia (South America), being this study a field evidence of the relevance of Bottom-Up as a main structuring factors of plankton abundance in these extreme environments.…”
Section: Controlling Factors Of Plankton Abundance In the Salinity Grsupporting
confidence: 56%
“…The absence of Top-Down effects and predominance of Bottom-Up forces in saline water systems, have been experimentally proved by Salms et al (2009) in the US saline lakes and Rejas et al (2012) in Bolivia (South America), being this study a field evidence of the relevance of Bottom-Up as a main structuring factors of plankton abundance in these extreme environments.…”
Section: Controlling Factors Of Plankton Abundance In the Salinity Grsupporting
confidence: 56%
“…Seasonal patterns of phytoplankton phyla changes in prairie saline lakes of the northern Great Plains (U.S.A.) were similar to those of freshwater systems [28], which these lakes were dominated by Cyanobacteria in the summer, with a shift to Bacillariophyta-dominated communities in the autumn. However, in Chagan Nur Lake were Bacillariophyta-dominated communities in the summer shift to Cyanobacteria-dominated in the autumn.…”
Section: The Interaction Between Phytoplankton Functionalmentioning
confidence: 84%
“…The relationship between the phytoplankton community and the water environmental parameters has been investigated in aquatic environments (Romo & Tongeren 1995;Gasiunaite et al 2005;Sun et al 2006;Suikkanen et al 2007;López-Flores et al 2009;Salm et al 2009;Bernardi Aubry et al 2013). Suikkanen et al (2007) reported that dissolved inorganic nitrogen was the major factor shaping the phytoplankton community structure in the open northern Baltic Sea.…”
Section: Discussionmentioning
confidence: 99%